2020
DOI: 10.1080/0312407x.2020.1808031
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Common Humanity Scenarios to Promote Compassion in Healthcare Workers

Abstract: The importance of compassion in healthcare is universally acknowledged. However, the factors that enhance compassion are not well understood. The perception of common humanity has been proposed as a prosocial perspective that leads to unbiased universal compassion. There has been a lack of research into the relationship between common humanity and compassion. This study examined the use of common humanity scenarios to promote compassion in healthcare workers. Seventy-five healthcare workers were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…As the historian Katharina von Kellenbach reported in her book The Mark of Cain, a brief eye contact between a Nazi perpetrator and a dying Jewish victim "humanized him [the victim] and made this scene unbearable to Zakis [the Nazi perpetrator]" (Von Kellenbach, 2013). Empirical studies have shown that paying attention to the feelings of stigmatized victims (e.g., individuals living with HIV) reduces desert-based prejudice (Batson et al, 1997;Zaki, 2019), and narratives on common humanity could promote compassion in healthcare workers (Baguley, Dev, Fernando, & Consedine, 2020;Ling, Olver, & Petrakis, 2020;Ling, Petrakis, & Olver, 2021;Sinclair et al, 2018). It would be important to examine if similar approaches would be effective for removing the moral barriers of compassion.…”
Section: Discussionmentioning
confidence: 99%
“…As the historian Katharina von Kellenbach reported in her book The Mark of Cain, a brief eye contact between a Nazi perpetrator and a dying Jewish victim "humanized him [the victim] and made this scene unbearable to Zakis [the Nazi perpetrator]" (Von Kellenbach, 2013). Empirical studies have shown that paying attention to the feelings of stigmatized victims (e.g., individuals living with HIV) reduces desert-based prejudice (Batson et al, 1997;Zaki, 2019), and narratives on common humanity could promote compassion in healthcare workers (Baguley, Dev, Fernando, & Consedine, 2020;Ling, Olver, & Petrakis, 2020;Ling, Petrakis, & Olver, 2021;Sinclair et al, 2018). It would be important to examine if similar approaches would be effective for removing the moral barriers of compassion.…”
Section: Discussionmentioning
confidence: 99%
“…As the historian Katharina von Kellenbach reported in her book The Mark of Cain, a brief eye contact between a Nazi perpetrator and a dying Jewish victim "humanized him [the victim] and made this scene unbearable to Zakis [the Nazi perpetrator]" (Von Kellenbach, 2013). Empirical studies have shown that paying attention to the feelings of stigmatized victims (e.g., individuals living with HIV) reduces desert-based prejudice (Batson et al, 1997;Zaki, 2019), and narratives on common humanity could promote compassion in healthcare workers (Baguley, Dev, Fernando, & Consedine, 2020;Ling, Olver, & Petrakis, 2020;Ling, Petrakis, & Olver, 2021;Sinclair et al, 2018). It would be important to examine if similar approaches would be effective for removing the moral barriers of compassion.…”
Section: Discussionmentioning
confidence: 99%
“…Tendo em vista que empatia e compaixão, dimensões do cuidado fundamentais ao profissional de saúde, podem ser desenvolvidas, além de relacionarem-se à autocompaixão. Alguns estudos (Ling et al, 2021;Mills, 2020)…”
Section: Discussionunclassified
“…Se empatia, sentimento aflorado pela dor do outro, e compaixão, desejo de aliviar o sofrimento alheio, são elementos basilares a toda pessoa que anseia por tornar-se um bom profissional de ajuda (Ling et al, 2021;Mills, 2020), a disponibilidade ao cuidado implica em afetar-se. Todavia, no alto grau de exposição a estressores traumáticos -como o sofrimento de outrem -há o risco do cuidador formal internalizar o que os pacientes sentem, o que pode comprometer a sua Qualidade de Vida Profissional (QVP), bem como o cuidado realizado por ele (Barbosa et al, 2014;Lago, 2008;Lago & Codo, 2013;Stamm, 2010;Toledo et al, 2015).…”
Section: Introductionunclassified